Agricultural Activities and the Madura Salt Industry in the Late 19th Century to the 1930s - Iswahyudi (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2023)
The colonial government's strong reason for continuing to pay special attention and evaluation to Madura was due to economic factors, namely the potential for large people's salt production and the potential for people's agriculture. The agrarian life for the Madurese has become a general trend, as is widely adopted in the economic system of the Indonesian people. This is evidenced by the fact that since the 17th century, Madura as a conquered area of the Mataram king Sultan Agung had the obligation to submit taxes every year in the form of one real, 10 pikul of rice and several pikul of fruit. This was corroborated by De Jonge who stated that until the next century the Madurese who still made a living as farmers included the majority of the population, namely around 70% - 80% of the total population, while the rest made a living as fishermen, even though this work actually required requirements. capital intensive. There is also the habit of the population to migrate out of the region, especially to plantation areas in Java as a workforce whose existence is clearly needed by plantation companies.